Efficacy and Safety of Socheongryong-Tang Among Atopic Dermatitis Patients With Respiratory Disorders: A Double-Blinded, Randomized, Placebo-Controlled Clinical Trial - Lee, Ju Hyun; Jo, Eun Heui; Jung, Jee Youn; Kim, Young-Eun; Son, Mi-Ju; Kang, Su Jin; Yang, Geum Jin; Shim, Yu Hwa; Park, Min Cheol (Frontiers in Pharmacology, 2020)
Atopic dermatitis is a chronic inflammatory skin disease that affects the growth and development of children. The prevalence of atopic dermatitis has been continually increasing, and this has also been accompanied by rising socioeconomic costs. Interest has been growing in alternative medicine as a means of alleviating the burden of atopic dermatitis. This was a single-center, double-blinded, randomized, placebo-controlled investigator-led clinical trial including 60 atopic dermatitis patients. The participants were classified into an experimental group (30 persons) and a control group (30 persons), who were administered, respectively, socheongryong-tang or a placebo for 4 weeks. After 4 weeks of treatment, the participants visited the trial center again and assess their efficacy and safety. The researchers performed statistical comparisons of the changes in the SCORAD Index, amount and frequency of ointment use, and height and weight to assess the efficacy. To assess the safety, diagnostic tests and vital sign checks were performed at each visit, and the presence or absence of adverse events was observed. As a result, the frequency and the amount of steroid ointment application in both groups increased, but the experimental group showed less tendency (P=0.081). Results of analyzing the children in the experimental group in relation to growth showed a significantly greater height growth than the control group (P<0.05). In addition, all study participants did not show any remarkable abnormal signs in the safety evaluation. In conclusion, compared to the control group, the experimental group, who took socheongryong-tang showed a tendency to be less dependent on steroid ointment and statistically significant increase in height.